Mejoramiento del desempeño laboral de los trabajadores del sector salud: el caso de Nicaragua - Cortez, Rafael (2011)
Ensuring adequate numbers of skilled and motivated health professionals is a serious policy issue in many developing and transitional countries. While quantitative data about workers migration and absenteeism is often available, qualitative evidence on factors that influence health workforce performance is scarce and can be valuable for health planners and policy makers. This article uses findings from focus group discussions with Nicaraguan health workers to identify performance problems, as well as their sources and potential solutions. The authors argue that the problems identified have been exacerbated by Nicaragua’s ongoing decentralization process, the lack of effective regulation and worker incentive system. To address the central issue of worker motivation, Health Ministry (Minsa) must accompany the decentralization process and the empowerment of the Public Local System of Health (Silais) on resource management, provide the inputs required by health services, promote the proper functioning of performance agreements which would improve the work culture in the sector, and res-establish professionalism within health care workers.